Qualidade do leite de vacas criadas no sistema silvipastoril no Vale do Cauca, Colômbia - Bolaños, Carmen A.d. [UNESP]; Pantoja, José C.f. [UNESP]; Alves, Ana C. [UNESP]; Risseti, Rafaela M. [UNESP]; Listoni, Fernando J.p. [UNESP]; Ribeiro, Márcio Garcia [UNESP] (Colégio Brasileiro de Patologia Animal - CBPA, 2014)
The silvopastoral system is characterized by increasing the production of milk with a greater number of cows per hectare due to the higher amount of protein in the diet. In silvopastoral system cows are fed in addition to pasture, small trees and shrubs. The aim of this study was determinate the main indicators of milk quality and mastitis causal agents in cows bred on silvopastoral system. We evaluated the composition (fat, total protein, lactose, solids, dry extract, nonfat dry and urea nitrogen), somatic cell count (SCC), total bacterial count (TBC), occurrence of clinical and subclinical mastitis, microbiological isolation, in vitro antimicrobial sensitivity profile and detection of antimicrobial residues in milk produced by 100 cows raised in silvopastoral systems, as well as the bulk tank and churns in farms of Cauca Valley, Colombia. The concentration of the major constituents of milk were 3.24% fat, 3.27% total protein, 4.40% lactose, 10.62% dry extract, 8.57% nonfat dry and 15.82mg/dL urea nitrogen, while the bulk tank and churns was 3.51% fat, 3.20% total protein, 4.34% lactose, 11.72% dry extract, 8.47% nonfat dry and 14.57mg/dL urea nitrogen. The cell count of the cows and the bulk tank was 141,252.75 CS/mL and 363,078.05 CS/mL respectively. The TBC mean in cows and the bulk tank was 4,466.84 CFU/mL and 24,547.01 CFU/mL respectively. The main microorganisms isolated from the udder cows were Corynebacterium bovis, Staphylococcus aureus, Staphylococcus hyicus, Staphylococcus spp., Streptococcus dysgalatiae, while the bulk tank were identified more often Streptococcus spp., Enterobacter cloacae, Hafnia alveii, hemolytic Streptococcus and Streptococcus spp. Antimicrobial residues in cow milk and bulk or churn were detected in 30% and 86% respectively. The silvopastoral system showed to be good alternative to milk production in cow. However is important the care with antimicrobial residues in milk and the analysis of all quality parameters to ensure a differentiated product.

O sistema silvipastoril caracteriza-se por aumentar a produção de leite, com maior número de vacas por hectare devido ao maior aporte de proteína na dieta. Neste sistema as vacas são alimentadas, além do pasto, de pequenas árvores e arbustos. O objetivo do presente estudo foi determinar os principais indicadores de qualidade do leite e agentes causais de mastite em vacas criadas em sistema silvipastoril. Foram avaliadas a composição (teor de gordura, proteína total, lactose, extrato seco, extrato seco desengordurado e nitrogênio uréico), contagem de células somáticas (CCS), contagem bacteriana total (CBT), ocorrência de mastite clínica e subclínica, isolamento microbiológico, perfil de sensibilidade bacteriana in vitro e detecção de resíduos antimicrobianos no leite produzido por 100 vacas, bem como do tanque de expansão e latões em propriedades do Vale do Cauca, Colômbia. Os teores médios dos principais constituintes do leite foram 3,24% de gordura, 3,27% de proteína total, 4,40% de lactose, 10,62% de extrato seco, 8,57% de extrato seco desengordurado e 15,82mg/dL de nitrogênio uréico, enquanto do tanque de expansão e latões foi 3,51% de gordura, 3,20% de proteína total, 4,34% de lactose, 11,72% de extrato seco, 8,47% de extrato seco desengordurado e 14,57mg/dL de nitrogênio uréico. A celularidade média dos quartos mamários e do tanque de expansão foi 141.252,75 CS/mL e 363.078,05 CS/mL respectivamente. A CBT média dos quartos mamários e do tanque de expansão foi 4.466,84 UFC/mL e 24.547,01 UFC/mL. Os principais micro-organismos isolados dos quartos mamários foram Corynebacterium bovis, Staphylococcus aureus, Staphylococcus hyicus, Staphylococcus spp., Streptococcus dysgalatiae, enquanto do tanque de expansão foram identificados Streptococcus spp., Enterobacter cloacae, Hafnia alveii, Streptococcus hemolítico e Streptococcus spp., com maior frequência. A presença de resíduos de antimicrobianos em leite de vacas e do tanque ou latão foi detectada em 30% e 86% das amostras, respectivamente. O sistema silvipastoril mostrou ser uma boa alternativa para produção de leite em vacas. No entanto, são necessários cuidados no tratamento mamário para evitar resíduos no leite e a análise de todos os parâmetros de qualidade para garantir um produto diferenciado.
Milk quality indicators from cows bred on silvopastoral system in Cauca Valley, Colombia
Keywords: Silvipastoril; bovino; mastite; CCS; CBT; resíduos de antimicrobianos; Silvopastoral; cattle; mastitis; SCC; TBC; antimicrobial residues